Employment impacts of petroleum industry in China: an input-output analysis. (1st January 2013) - Tang, Xu; Zhang, Baosheng; Wei, Xinqiang; Höök, Mikael
China's employment issue is catching people's eyes at present and for a long time. Economic impacts of China's petroleum industry on employment are divided into direct, indirect and induced impacts and they are analysed in this study by using the input-output approach. The research results suggest that petroleum industry will supply 0.0957 jobs and 0.1501 jobs given 10, 000 CNY final demand added in extraction of petroleum and processing of petroleum respectively; 1, 887 CNY and 2, 756 CNY of employment income will be affected given 10, 000 CNY final demand added in extraction of petroleum and processing of petroleum respectively; extraction of petroleum has more direct impact on both employment number and employment income given one unit output added, and processing of petroleum has more indirect and induced impact on them. The petroleum industry's impact coefficients on both employment number and employment income have been decreasing since 1987. The proportion of direct impacts in total impacts continues to decrease, and the connection between petroleum industry and other sectors in China's national economy has become closer than before.